ANALISIS PENGARUH CASH POSITION, DEBT TO EQUITY RATIO, DAN RETURN ON ASSETS TERHADAP DIVIDEN PAYOUT RATIO PADA PERUSAHAAN- PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012 – 2014 - Annisa Trilestari; Desta Rizky Kusuma (Universitas Ahmad Dahlan, 2016)
This research was conducted to examine the effect of variable cash sition, debt to equity ratio, and return on assets on dividen payout ratio on compnies listed on the Indonesian Stock Exchane 2012 – 2015 periode. The population in research is all companies listed on the Indonesian Stock Exchange 2012 – 2015 periode. The number of samples used for a many as 59 companies with used purposive sampling. Data obtained from the publication of Indonesian Capital Market Directory (ICMD). The analysis technique used data penel regression and hypothesis testing using the t statistik and koefisien determination with the 5% level if confidence.The results showed that the cash position has a significant effect on the dividen payout ratio with a positive direction. While the debt to equity ratio has a significant effect on the dividen payout ratio with a negative direction. Meanwhile, the return on assets have no significant effect on the dividen payout ratio. Based on a statistical analysis of significance of t cash position values obtained 0,0233 (less than 0,05) and values significance for debt to equity ratio obtained 0,0007 (less than 0,05). While return on assets have a significance values obtained 0,5209 (than 0,05), so it can be concluded that variable cash position and debt to equity ratio have a significant influence on dividen payout ratio. While return on assets have no significance influnce on dividen payout ratio. From Adjusted R² value of 0,054332 indicates that there are independent variable in the model can explain influence on dividen payout ratio by 5, 43% , while 94,57% residual explain bay the dividen payout ratio of other variables outside the model.